CORTICOSTEROIDS - (UN)PREDICTABLE INDUCERS OF PSYCHIATRIC DISORDERS - Tatyana Telbizova; Mariana Arnaoudova (Peytchinski Publishing, 2019)
Synthetic corticosteroids are a widely used and highly effective group of drugs for the treatment of a number of diseases. They have the potential to induce a broad spectrum of psychotic disorders that are often misdiagnosed, underestimated and unpredictable. Objective: The aim of the present article is to report two cases of corticosteroid-related psychotic disorders. The first case was a patient who has undergone allogeneic bone marrow transplantation, followed by an oral administration of prednisolone with an initial daily dose of 100 mg, subsequently reduced by 10 mg per week. Upon reaching a dose of 50 mg daily, the patient suddenly became psychomotor agitated, in an elevated mood, with ecstatic and megalomaniac experiences. Prednisolone treatment was discontinued, and olanzapine was initiated at doses of 10 mg/day and diazepam at 10 mg/night. Within 5 days, the described psychopathological symptoms were de-actualized, and the antipsychotic treatment was discontinued. The second case was a patient who was on a supportive treatment of four accompanying autoimmune diseases with methylprednisolone 4 mg/day and developed anxiety-depressive symptoms. Administration of Milnacipran at a maintenance dose of 100 mg/day led to significant reductions in depression and anxiety. Conclusion: Corticosteroids have a high potential to induce a wide range of mental disorders. Clinicians and patients should be aware of these adverse effects. Inability to stop the corticosteroid treatment in many cases requires the use of psychotropic medications. Both drug interactions and the potential side effects need to be taken into consideration.